2019
DOI: 10.1080/20477724.2019.1710066
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of M. tuberculosis Beijing genotype in Latin America and the Caribbean

Abstract: Lineage 2 (East Asian), which includes the Beijing genotype, is one of the most prevalent lineages of Mycobacterium tuberculosis (Mtb) throughout the world. The Beijing family is associated to hypervirulence and drug-resistant tuberculosis. The study of this genotype's circulation in Latin America is crucial for achieving total control of TB, the goal established by the World Health Organization, for the American sub-continent, before 2035. In this sense, the present work presents an overview of the status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 166 publications
1
14
2
Order By: Relevance
“…The European origin and the influence of European settlers in America and Colombia are confirmed. Similar results have been described by other authors in regions of the country such as Cali [ 33 ] Bogotá [ 34 ] and Medellín [ 35 ]. Contrary to these reports, in Buenaventura, a region of Valle del Cauca, the Beijing lineage, clearly associated with resistant cases has been identified [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The European origin and the influence of European settlers in America and Colombia are confirmed. Similar results have been described by other authors in regions of the country such as Cali [ 33 ] Bogotá [ 34 ] and Medellín [ 35 ]. Contrary to these reports, in Buenaventura, a region of Valle del Cauca, the Beijing lineage, clearly associated with resistant cases has been identified [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The Beijing genotype is frequently associated with antibiotic resistance and immune evasion, allowing high bacterial replication, dissemination, and transmission [44][45][46]. Interestingly, the Beijing genotype is not frequent in Latin America (incidence less than 5%) [47]. The Beijing lineage in Colombia has been circulating in the southwest of the country since 1998 [48].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study in Latin America found a low prevalence of Beijing genotypes. A prevalent trend of less than 5% was found, except for Cuba (17.2%), Peru (16.0%) and Columbia (5%) 9 . Sub-typing of a large group of Beijing strains and clusters of non-Beijing genotypes can be achieved by the mycobacterial interspersed repetitive unit-variable number tandem repeat (MIRU-VNTR) analysis [10][11][12] .…”
Section: Introductionmentioning
confidence: 87%